2009
DOI: 10.1021/la904007m
|View full text |Cite
|
Sign up to set email alerts
|

Surface Potentials in Langmuir Monolayers of Unidirectionally Oriented α-Helical Diblock Copolypeptides

Abstract: The surface potentials and effective dipole moments of alpha-helical amphiphilic diblock copolypeptides during monolayer compression at the air-water interface are reported. Amphiphilic diblock copolypeptides (PLGA-b-PMLGSLGs) of poly(alpha-L-glutamic acid) (PLGA) and poly(gamma-methyl-L-glutamate-ran-gamma-stearyl-L-glutamate) with 30 mol % of stearyl substituents (PMLGSLG) of various block lengths were studied during the double-brush formation process at the water surface. Upon monolayer spreading of PLGA-b-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…21 The compression-decompression of these monolayers is a reversible process with a large hysteresis upon monolayer compression to a pressure above the second transition and no hysteresis before this transition. 30 The linear increment in surface pressure following the first transition in the isotherms of PLGA-b-PMLGSLGs corresponds to the packing and tilting of the PMLGSLG block segments away from the water surface after the PLGA block is immersed. Assuming the same maximum compression of the PMLGSLG blocks for all of the PLGA-b-PMLGSLGs (i.e.…”
Section: Surface Pressure-area (P-a) Isothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The compression-decompression of these monolayers is a reversible process with a large hysteresis upon monolayer compression to a pressure above the second transition and no hysteresis before this transition. 30 The linear increment in surface pressure following the first transition in the isotherms of PLGA-b-PMLGSLGs corresponds to the packing and tilting of the PMLGSLG block segments away from the water surface after the PLGA block is immersed. Assuming the same maximum compression of the PMLGSLG blocks for all of the PLGA-b-PMLGSLGs (i.e.…”
Section: Surface Pressure-area (P-a) Isothermsmentioning
confidence: 99%
“…We have measured the surface potentials of the PLGA-b-PMLGSLG monolayers during compression at the air-water interface. 30 The results showed that the polypeptide macrodipole moment immersed in water was effectively screened out. However, the effective dipoles of the a-helices of the hydrophobic block tilted away from the water surface were largely maintained and related increasingly to DP PMLGSLG .…”
Section: Surface Pressure-area (P-a) Isothermsmentioning
confidence: 99%
“…Besides the high mobility provided by the amorphous side chain mantle of the hairy-rod polypeptide block, monolayers of these diblock copolypeptides exhibit a brush structure composed of densely packed parallel R-helices, which are tilted at an angle with respect to the water surface normal. [30][31][32] Interestingly, we observed strong effects of in-plane anisotropy produced by the transfer process in the LB monolayers of these diblock copolypeptides. Particularly, a dipping-induced helix orientation oblique by an angle with respect to the dipping direction was observed for the first time.…”
Section: Introductionmentioning
confidence: 79%
“…(BG-NCA) 11.85 g of BG (0.05 mol) was dissolved in 100 mL of dry THF. 19.0 mL of α-pinene (0.12 mol, 1.2 eq.)…”
Section: Synthesis Of Benzyl L-glutamate-ncamentioning
confidence: 99%
“…Alternatively, PG has been chemically prepared via amine-initiated ring-opening polymerization of a γ-R-L-glutamate N-carboxyanhydride (NCA) monomer, with R is an acid labile blocking group such as the tert-butyl or piperonyl protecting group 9,10 . However, the ring-opening polymerization of glutamate NCA monomers bearing these substituents often resulted in polyamides with relatively low molecular weights low yields 9,11 . Moreover, although these carboxylic protected polyglutamates can be in the α-helix conformation, the PGs resulted after removal of the protected groups have low molecular weights and hence a high propensity for forming β-sheet aggregates.…”
Section: Introductionmentioning
confidence: 99%